Post-match recovery profile of leukocyte cell subsets among professional soccer players - Kostrzewa-Nowak, D.; Wityk, P.; Ciechanowicz, A.; Nowak, R. (Scientific Reports, 2021)
This study assessed the impact of cumulative match time on the distribution of CD45+ cell subtests in the capillary blood of professional soccer players. Twenty-two males (aged 18-30 years) took part in the 36-week study. Participants playing up to 540 in cumulative match time and less than 30 min in each single match during the observation period formed the control group. White blood cell (WBC) phenotyping and creatine kinase (CK) plasma activity analyses were performed. Also, counts for WBC subsets were determined. No significant differences in the hematological parameters or lymphocyte and NK cell percentages were observed between the control and study groups. Changes in the T cell percentage were significant during weeks 11 and 30 and in Th and Tc cell percentages during weeks 2 and 26. Significant correlations were found between the cumulative match time and Th, NK, and B cell percentages; monocyte counts; and CK activity in the control group. However, for the study group, correlations were found between cumulative match time and Th, Tc, and B cell percentages; CK activity; and the CK ratio. Our study suggests that the distribution of CD45+ cells might be a useful tool for monitoring the immune status of professional soccer players.